Effect of the Particle Orientation on the Magneto-Rheological Behaviour of Carbonyl Iron Powder-Filled Natural Rubber - Lee, Junwan; Park, Moonsu; Chung, Kyungho; Yoon, Jihyun; Oh, Jaeeung; Kim, Minsoo; Lee, Seonghoon (Asian Journal of Chemistry, 2013)
Compared to a conventional rubber vibration isolator, a magneto-rheological elastomer (MRE) can absorb a broader frequency range of vibrations. The characteristic phenomena results from the orientation of magneto responsible particles via chain-like formation in a rubber matrix. In this study, natural rubber was used as the matrix to manufacture magneto-rheological elastomers. Carbonyl iron powder, which has a rapid magnetic reaction, was selected as the magnetic particle to create a magnetic field reactive modulus. The mechanical properties of the manufactured magneto-rheological elastomers were measured without the application of a magnetic field. With the addition of carbonyl iron powder, the tensile property decreased and the hardness increased. The magneto-rheological effect was analyzed using a fast Fourier transform analyzer with various magnetic fluxes. The magneto-rheological effect also increased with increasing carbonyl iron powder content and magnetic flux. In addition, the carbonyl iron powder loading affected the mechanical properties of magneto-rheological elastomer. A modulus variable vibration isolator can be developed if the mechanical properties and manufacturing process of magneto-rheological elastomer are controlled properly by the magnetic field.